An Analysis of Students’ Difficulties in Writing Recount Text: A Case Study at The Eleventh Grade Students of MA Putra Al-Ishlahuddiny Kediri Academic Year 2016/2017 - Heni Yuni Mustika; Udin Udin; Ni Wayan Mira Susanti (Indonesian Publication Center, 2020)
This thesis entitled “An Analysis of Students’ Difficulties in Writing Recount Text: A Case Study at the Eleventh Grade Student of MA Putra Al-Ishlahuiddiny Kediri Academic Year 2016/2017”. It was aimed to know students’ difficulties and the factors contributing to those difficulties in writing recount text. There were 36 out of 135 students who were taken by using purposive sampling as samples (XI IPA 2). In data collection, three kinds of instruments were used: test, questionnaire and interview. The test was used to know students’ difficulties in writing recount text. The questionnaire was divided into open and close ended questions to obtain information about the factors contributing to the students’ difficulties in writing recount text. The Interview was used as an additional input to complete the data. This study used quantitative and qualitative descriptive method to analyze the data. From the analysis it was found that students were generally categorized as mean score with the percentage is (50.69%) by seeing students’ difficulties in content, organization, vocabulary and sentence structure in term of the test conducted. In terms of the questionnaires, the result showed that the most dominant difficulties were the making of past tense sentences and distinguishing regular from irregular verbs with percentage (81%). Whereas the interview result found that most of students did not understand how to write a recount text and how to use proper words and that they had lack of vocabulary